Does Board Gender Diversity Make a Difference? New Evidence from Quantile Regression Analysis - Dang, Rey; Nguyen, Duc (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2016)
This article examines the link between board gender diversity and firm performance from a dynamic perspective through quantile regression, which allows us to capture the potential impact of female representation at different points of the distributions of the performance measure. Our results from a panel of French listed companies (SBF 120) show that the impact of board gender diversity on firm performance differs across quantiles and depends on the measure of performance under consideration. Typically, board gender diversity affects negatively the Tobin’s Q and positively the return on asset when these variables are high and low, respectively.JEL classification: G30; G34; J16